Dari Bermain ke Praktik Sosial: Pembelajaran Role Play dan Pembentukan Kompetensi Komunikasi di Komunitas Pinggiran Indonesia - Pattiasina, Jefri Natanael; Afdhal, Afdhal (Universitas Pattimura, 2022)
This study examines the contribution of role play learning methods to the development of interpersonal communication competence among early childhood learners in peripheral regions of Indonesia, focusing on TK Ilwiaru Watumera Wakarleli in Southwest Maluku. Framed within participatory pedagogy, symbolic interactionism, and social reproduction theory, the study positions role play not merely as a learning activity but as a form of social practice that shapes children’s communicative habitus within their local cultural context. Using a qualitative case study approach, data were collected through participant observation, in-depth interviews, and documentation of classroom activities. Findings reveal that role play significantly facilitates early socialization, strengthens children's capacity as reflective social actors, and fosters interactional dynamics reflecting the norms, values, and social structures of the local community. This research contributes novel insight by highlighting the transformative potential of symbolic play in early childhood education in Indonesia’s frontier, outermost, and underdeveloped (3T) areas—not only as a medium for reproducing existing structures but also for initiating social change. The study advocates for context-based, culturally grounded early childhood curricula that support inclusive communication skills and align with broader efforts toward the decolonization of education in the social and political sciences.